Efek Iradiasi Gamma Terhadap Aktivitas Inhibisi Xantin Oksidase Secara In Vitro pada Sediaan Jamu Anthiperurisemia Daun Sendok, Seledri dan Cabe (SESEJA) - Nuraini, Nuraini; Fahrezi, Fahrul Arya; Arini, Arini Aprilliani (Universitas Borneo Lestari, 2025)
Plants such as broadleaf plantain, celery, and java long peppers are known to lower uric acid levels, inhibit xanthine oxidase, and have analgesic effects. The process of food irradiation is used to preserve and improve food safety. This study aimed to determine the inhibition activity of xanthine oxidase before and after 10 kGy gamma irradiation in herbal medicine, by testing category I ionizing irradiation (Gamma Chamber & Gamma Cell) at a dose of 10 kGy and Elabscience® Xanthine Oxidase (XOD) Activity Assay Kit, in various concentrations (4 μg/mL; 8 μg/mL; 16 μg/mL; 31 μg/mL; 63μg/mL) with allopurinol as a comparator. The results showed that allopurinol had a very strong inhibitory activity against the enzyme xanthine oxidase, with an IC50 value of (1,445 μg/mL). Antihyperuricemia herbs before and after gamma irradiation of 10 kGy have the potential to be xanthine oxidase inhibitors at concentrations (4 μg/mL; 8 μg/mL; 16 μg/mL; 31 μg/mL; 63 μg/mL). Irradiation of 0 kGy showed weaker inhibitory activity compared to allopurinol, but was still very strong with an IC50 value of (24.548 μg/mL). Meanwhile, 10 kGy irradiation has stronger inhibitory activity than 0 kGy irradiation samples, with an IC50 value of (15.295 μg/mL). This suggests that a dose of 10 kGy has a higher potential in inhibiting the activity of the enzyme xanthine oxidase compared to a dose of 0 kGy.